PENGARUH PROFITABILITAS, UKURAN PERUSAHAAN DAN KINERJA LINGKUNGAN TERHADAP CORPORATE SOCIAL RESPONSIBILITY DISCLOSURE BERDASARKAN INDIKATOR GLOBAL REPORTING INITIATIVE (GRI) PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Triana Zuhrotun Aulia (Universitas Muhammadiyah Tangerang, 2018)
Corporate Social Responsibility (CSR) is a transparent business practices, which are based on ethical values, by giving attention to the employees, society and environment, and designed to meet the wishes of shareholders and also society in general. This research is based on the belief (ontology) that CSR is a form of responsibility-oriented businesses in the fulfillment of public expectations concerning the existence of a company's business in the hope of obtaining legitimacy from the public. This study is a research conducted on manufacturing companies in Indonesia. The purpose of this study was to determine the factors that affect the disclosure of CSR in the annual reports of manufacturing companies in Indonesia. The data used total 18 companies that are listed in Indonesia Stock Exchange 2014-2016 or 90 firms-years. The sample is obtained by using purposive sampling method. Data collection method used was content analysis of social disclosures in corporate annual reports. Content analysis was conducted using a check list of items of social disclosure in corporate annual reports. Statistical method used is a multiple regression with eviews 9.0. The result of this study indicates that CSR disclosure practices as a field of coverage is significantly influenced by company size and environmental performance. Other factors examined in this study, such as profitability did not affect CSR disclosures made by companies.